MEDIA PEMBELAJARAN AGAMA ISLAM DI ERA MILENIAL 4.0 - Muhammad Zaim (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
Every industrial revolution will affect all aspects of life including Islamic education, as will the current industrial revolution 4.0 which has, is and will continue to influence all aspects of Islamic education, including influencing of learning media in Islamic education, and it is impossible for us to almost avoid this influence. Each influence brings positive and negative sides, and which will always be studied, how to maximize the positive side and minimize or avoid the negative side. This study will discuss how is the concept of Islamic learning media in this milenial era. This research is a qualitative research with descriptive analysis technique by using library research design. The results of this study reveal that learning media for the industrial era 4.0. namely technology-based learning media of the industrial era 4.0 is the right learning media for learning of students in this milenial era such as social media which incidentally is very familiar among the students. Considering this problem is a problem that the world of education is currently facing, this study is a very important to be constantly examined by Islamic religious education experts.